Application of lean warehousing strategies in footwear trading smes: a case study on enhancing operational efficiency in Peru - Ramirez Vizarreta, Tamara Belen (2025)
The footwear industry, particularly among SMEs in Peru, faces significant challenges in warehouse management, contributing to inefficiencies that affect overall competitiveness. Current research in Lean Warehousing highlights the potential for these practices to improve operational efficiency, yet the application in SMEs remains underexplored. The primary challenges addressed include excessive travel distances in picking, high cycle times, and low dispatch efficiency, which were critical to resolve for enhanced productivity. This study proposes a Lean Warehousing model tailored to SMEs, integrating Systematic Layout Planning and standardized work practices to optimize warehouse operations. Results indicated a 45% reduction in picking distance, a 26.47% decrease in cycle time, and a 4.17% improvement in office efficiency. These outcomes not only validated the model’s effectiveness but also demonstrated its potential to significantly improve the operational efficiency of SMEs in the footwear sector. The findings offer valuable insights for academics and practitioners, emphasizing the need for further exploration of Lean Warehousing in SME contexts to enhance industry competitiveness